Persepsi Warga Binaan Terhadap Ketersediaan Koleksi Islami Di Perpustakaan Lembaga Pemasyarakatan Kelas IIB Kota Solok - Putri, Annisa Rahman; Erlianti, Gustina (Scinary, 2024)
This research aims to examine the perceptions of inmates towards Islamic collections in the Class IIB Correctional Institution Library in Solok City. This research uses a quantitative type of research using descriptive methods. The population in this study were all inmates who borrowed Islamic collections from the library, namely a sample of 52 respondents. To collect data using a questionnaire. The results of this research are: (1) Relevance, obtaining an average of 2.59 categorized as good; (2) Recency, getting an average of 2.43 is considered not good; (3) Title ratio, getting an average of 2.85 which is categorized as good; (4) Quality, getting an average of 3.0 is considered good: (5) Scientific objects, getting an average of 3.25 is considered very good. Based on the overall average obtained, namely 2.78, it is categorized as quite good, but it needs improvement and support according to the number of users, number of titles and budgets from various parties in order to get satisfactory results.